DEIXIS IN ‘AKU KESEPIAN, SAYANG. DATANGLAH, MENJELANG KEMATIAN’ BY SENO GUMIRA AJIDARMA - RIESMAYANTI, DEVITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
The researcher interested in analyzing the relevancy of Levinson‟s theory withIndonesian literature, especially short story entitled Aku Kesepian, Sayang. Datanglah,Menjelang Kematian. In this research, there are two problems: (1) what kinds of deixis are usedin Aku Kesepian, Sayang. Datanglah, Menjelang Kematian by Seno Gumira Ajidarma? and (2)what are the meanings of the deictic expressions? The researcher uses a qualitative method sincethe research concerns with the application of language style to the written text. In this study, theresearcher finds that in three short stories, Kyoto Monogatari, Legenda Wongasu, and LayangLayangthere are five types of deixis: person deixis, place deixis, time deixis, discourse deixis,and social deixis.Keywords: Pragmatics, Deixis, Short Story